Disclosure Quality Assessment of Sustainability Reporting Practices in Emerging Countries: Case of Indonesia’s Banking Sector - Maftuchah, Istiana; Pramono, Teddie; Bachtiar, Novita (Otoritas Jasa Keuangan, 2023)
Indonesia has become a major force in advancing sustainable finance across emerging countries. One of the reasons was due to the role of the regulator and supervisor of Indonesia’s financial services industry, Indonesia Financial Services Authority, who required, through its regulation, Financial Services Institutions, Issuers and Public Companies to submit sustainable reports to Indonesia FSA and publish them for the public. This study is intended to conduct an assessment on the scope of disclosure presented on the sustainability report submitted by the Indonesian banking industry. The methodology used is qualitative with descriptive analysis. The evaluation was conducted through a desk study by analyzing banks’ sustainability reports available on their websites. The results of the analysis demonstrated that two years before the implementation of the Indonesia FSA sustainable finance regulation, only 28,5% of sustainability reports, which have submitted voluntarily by large commercial banks, are in line with materiality and stakeholders’ engagement principles. After the sustainable finance regulation was implemented, it was found that only 56,6% of the sustainability reports submitted met the materiality and stakeholders’ engagement principles required by the regulation. Therefore, the biggest challenge lies in the effort to promote awareness and understanding on the importance of sustainable finance and the quality of sustainability report disclosure.